Electronic tagging of Atlantic bluefin tuna (Thunnus thynnus, L.) reveals habitat use and behaviors in the Mediterranean Sea. - Pablo Cermeño; Gemma Quílez-Badia; Andrés Ospina-Alvarez; Susana Sainz-Trápaga; Andre M Boustany; Andy C Seitz; Sergi Tudela; Barbara A Block (PLoS ONE, 2015)
We analyzed the movements of Atlantic tuna (Thunnus thynnus L.) in the Mediterranean Sea using data from 2 archival tags and 37 pop-up satellite archival tags (PAT). Bluefin tuna ranging in size from 12 to 248 kg were tagged on board recreational boats in the western Mediterranean and the Adriatic Sea between May and September during two different periods (2000 to 2001 and 2008 to 2012). Although tuna migrations between the Mediterranean Sea and the Atlantic Ocean have been well reported, our results indicate that part of the bluefin tuna population remains in the Mediterranean basin for much of the year, revealing a more complex population structure. In this study we demonstrate links between the western Mediterranean, the Adriatic and the Gulf of Sidra (Libya) using over 4336 recorded days of location and behavior data from tagged bluefin tuna with a maximum track length of 394 days. We described the oceanographic preferences and horizontal behaviors during the spawning season for 4 adult bluefin tuna. We also analyzed the time series data that reveals the vertical behavior of one pop-up satellite tag recovered, which was attached to a 43.9 kg tuna. This fish displayed a unique diving pattern within 16 days of the spawning season, suggesting a use of the thermocline as a thermoregulatory mechanism compatible with spawning. The results obtained hereby confirm that the Mediterranean is clearly an important habitat for this species, not only as spawning ground, but also as an overwintering foraging ground.